2015
DOI: 10.5201/ipol.2015.44
|View full text |Cite
|
Sign up to set email alerts
|

An Implementation of Combined Local-Global Optical Flow

Abstract: Optical Flow (OF) approaches for motion estimation calculate vector fields for the apparent velocities of objects in image sequences. In 1981 Horn and Schunck (HS) introduced two basic assumptions: "brightness value constancy" and "smooth variation" to estimate a smooth OF field over the entire image -global approach-. In parallel, Lucas and Kanade (LK) assumed constant motion patterns for image patches, estimating piecewise-homogeneous OF fields -local approach-. Several variations of these approaches exist t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The CLG method (30,31) combines the HS method and a second method called Lucas-Kanade (LK). LK method assumes the constancy of motion in the neighborhood of a pixel i.e.…”
Section: Combined Local-global (Clg) Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CLG method (30,31) combines the HS method and a second method called Lucas-Kanade (LK). LK method assumes the constancy of motion in the neighborhood of a pixel i.e.…”
Section: Combined Local-global (Clg) Methodsmentioning
confidence: 99%
“…Takagaki et al 2011 (29) developed and reported a new method (Temporospatial -TS) in which temporal correlation of a given pixel with neighboring pixels was used to estimate local motion in voltage sensitive dye (VSD) imaging data. Recently, Mohajerani et al 2013 (16) used the combined local-global (CLG) algorithm (30,31) to determine velocity vector fields of flow in wide-field VSD imaging data. They also manually determined the location of sources and sinks in space and time.…”
Section: Introductionmentioning
confidence: 99%
“…This toolbox allows us to estimate the spatiotemporal dynamics, such as trajectory and speed, of pixels in our VSD recordings, using a variety of optical flow analysis methods. We used the Horn-Schuck (HS) method 27,61 for our optical flow analysis, and repeated select analyses with the Combined Local-Global (CLG) method, which combines the HS method with the Lucas-Kanade (LK) method 27,62,63 . The main difference between these methods is that the LK method assumes a pixel's motion is constant relative to neighboring pixels, whereas the HS method does not make this assumption 27 .…”
Section: Optical Flow Analysismentioning
confidence: 99%
“…In previous works, matrix splitting methods have often been used. Horn & Schunck rely on a Jacobi-like iteration, while Jara-Wilde et al use a socalled Pointwise-Coupled Gauss-Seidel in [8]. Krylov methods such as Conjugate Gradient (CG) can be found in [4].…”
Section: Solvers Reviewmentioning
confidence: 99%